Applying nanotechnology to the desulfurization process in petroleum engineering - Saleh, Tawfik A. (Advances in chemical and materials engineering (ACME) book series., 2016)
"This book explores recent developments in the field, including the use of nanomaterials for biodesulfurization and hydrodesulfurization"--